Controversies in Teaching: A review essay - Portelli, John P. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1986)
William Hare. CONTROVERSIES IN TEACHING. London, Ontario: The Althouse Press, 1985. 139 pp. $8.95.